Effect of long-term administration of sildenafil on lipid profile and organ functions in hyperlipidemic rats - El-Mahmoudy, Abubakr M.; Shousha, Saad M.; Abdel-Maksoud, Hussein; AbouZaid, Omayma (Acta Biomedica Atenei Parmensis, 2013)
The aim of the present study was to elucidate the possible biochemical alterations in lipid metabolic profile and organ function profiles that may result from continuous treatment with the drug, sildenafil in normal and hyperlipidemic rats. Blood samples were taken for biochemical analysis on days 30, 45 and 60 of the experiment. Sildenafil (5.625 mg/kg) significantly decreased the serum lipid parameters including total lipid, triacylglycerols, cholesterol, HDL-C, LDL-C, VLDL-C concentrations of rats fed on fat-enriched diet. However, it increased their values in serum of negative control rats. In addition, administration of sildenafil to normal rats caused insignificant changes in serum liver enzymes ALT and AST concentrations all over the period of the experiment; as well as serum urea and creatinine; yet, it significantly decreased their serum concentrations in animals fed on fat-enriched diet compared to the +ve untreated ones, upon its administration starting from the 30th day of the experiment.However, concurrent administration of sildenafil with highfat diet (group-iv) failed to guard against the rise in such liver and kidney function biomarkers. These data suggest that sildenafil may act as a mixed blessing drug; therefore it must be used carefully and under physician supervision to get its therapeutic benefits and guard against its adverse effects.